2009
DOI: 10.1007/s10562-009-0204-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of V2O5 Loading on Propane Combustion over Pt/V2O5–Al2O3 Catalysts

Abstract: Propane combustion was studied on Pt(0.4%)/ V 2 O 5 -Al 2 O 3 catalysts containing up to 20% V 2 O 5 . The density, strength and nature of surface acid sites were determined by TPD of NH 3 and FTIR spectra of adsorbed pyridine. The sample acidity increased with the vanadium content, essentially because the addition of vanadium oxide generated Brønsted acid sites. The Pt dispersion as determined by H 2 chemisorption increased with increasing V 2 O 5 loading. The sample activity for propane combustion was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…The increase in the fraction of oxidized platinum atoms to all the exposed ones on the former might cause the low TOF. The TOF of platinum catalyst reported on literatures varied for 25-39,300 over Pt/Al 2 O 3 and Pt/Beta, respectively [16,38]. The reaction conditions and the conversion levels for determining TOF were varied according to the literatures.…”
Section: The Combustion Of Propane Over the Platinum Catalystsmentioning
confidence: 99%
“…The increase in the fraction of oxidized platinum atoms to all the exposed ones on the former might cause the low TOF. The TOF of platinum catalyst reported on literatures varied for 25-39,300 over Pt/Al 2 O 3 and Pt/Beta, respectively [16,38]. The reaction conditions and the conversion levels for determining TOF were varied according to the literatures.…”
Section: The Combustion Of Propane Over the Platinum Catalystsmentioning
confidence: 99%
“…Over the last few years, some studies have also been focused on the catalysts with combination of a noble metal and a base metal oxides for VOCs oxidation reactions. For example, tungsten [13], vanadium [2,14] and niobium [15] oxides have been used and they are known to promote the activity of metal catalysts (Pd, Pt) for VOCs oxidation. It has been accepted that the positive promoting role of various modifiers for oxidation of alkanes, is generally attributed to a range of different factors, such as controlling the noble metal particle size, catalyst reducibility and metal oxidation state [16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted on propane combustion over different catalysts, viz., non-noble metal oxides [4][5][6] and supported noble metals including Pt [7][8][9][10][11][12][13], Pd [14,15], Au [10,16], and Rh [17]. To maximize the energy efficiency and minimize the thermal NO x formation, it is desirable to develop a catalyst that will be active at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Ishikawa et al [19] explained a high catalytic activity for propane combustion over Pt catalysts supported on solid superacids by the strong surface acidity of the support. Propane combustion over Pt catalysts on various supports, viz., MgO [11], Al 2 O 3 [11], SiO 2 -Al 2 O 3 [11,20], WO 3 [13], zeolite [21,22], TiO 2 -SiO 2 [23], and V 2 O 5 -Al 2 O 3 [7] has been examined. It has been reported that the activities of Pt catalysts on supports having high acidities was superior to those of Pt catalysts on supports having lower acidities, because the surface acidity of a support was considered to be a factor in the changing of the oxidation state of Pt [11,12,20,21,24].…”
Section: Introductionmentioning
confidence: 99%